2022
DOI: 10.3390/nu14153019
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns Derived from Reduced Rank Regression Are Associated with the 5-Year Occurrence of Metabolic Syndrome: Aichi Workers’ Cohort Study

Abstract: The aim of the present study was to derive dietary patterns to explain variation in a set of nutrient intakes or in the measurements of waist circumference (WC) and fasting blood glucose (FBG) using reduced rank regression (RRR) and to prospectively investigate these patterns in relation to the risk of developing metabolic syndrome (MetS) and its components during the follow-up. The study participants were comprised of 2944 government employees aged 30–59 years without MetS. RRR was applied with 38 food groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…A case-control study on patients with type 2 DM in Tabuk City, Saudi Arabia, showed that fast food intake (p<0.001), fruit consumption (p=0.004), and breakfast skipping (p<0.001) were positively associated with diabetes, while sweet food consumption was negatively associated with diabetes control (p=0.046) [ 12 ]. One cohort study reported that a healthy diet was negatively associated with metabolic syndrome (p=0.009) and hypertension (p= 0.002), while an unhealthy diet was associated with all of its components (insulin resistance, high blood triglycerides, low levels of HDL cholesterol, obesity, and high blood pressure) (p<0.05), increasing risks for type 2 DM [ 27 ]. Two articles (one cohort and one cross-sectional) reported a positive association between a plant-based diet and good diabetic management [ 28 ], reduced triglyceride levels, and increased HDL levels [ 29 ].…”
Section: Reviewmentioning
confidence: 99%
“…A case-control study on patients with type 2 DM in Tabuk City, Saudi Arabia, showed that fast food intake (p<0.001), fruit consumption (p=0.004), and breakfast skipping (p<0.001) were positively associated with diabetes, while sweet food consumption was negatively associated with diabetes control (p=0.046) [ 12 ]. One cohort study reported that a healthy diet was negatively associated with metabolic syndrome (p=0.009) and hypertension (p= 0.002), while an unhealthy diet was associated with all of its components (insulin resistance, high blood triglycerides, low levels of HDL cholesterol, obesity, and high blood pressure) (p<0.05), increasing risks for type 2 DM [ 27 ]. Two articles (one cohort and one cross-sectional) reported a positive association between a plant-based diet and good diabetic management [ 28 ], reduced triglyceride levels, and increased HDL levels [ 29 ].…”
Section: Reviewmentioning
confidence: 99%